1999
DOI: 10.1148/radiology.210.1.r99ja10163
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea Syndrome: Hooked Appearance of the Soft Palate in Awake Patients—Cephalometric and CT Findings

Abstract: Cephalometric radiography and CT can demonstrate hooking of the soft palate in awake patients. This finding indicates a high risk for OSAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
2
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 34 publications
6
34
2
6
Order By: Relevance
“…We found that 63.1% of the patients (12/19) had enlarged soft palates (reference value: 34G6 mm) (15).…”
Section: Clinical and Laboratory Patients' Profilementioning
confidence: 70%
See 1 more Smart Citation
“…We found that 63.1% of the patients (12/19) had enlarged soft palates (reference value: 34G6 mm) (15).…”
Section: Clinical and Laboratory Patients' Profilementioning
confidence: 70%
“…1). There are no established normal ranges for all these measurements, except for the length of the soft palate, for which the reference value is 34G6 mm (15).…”
Section: Cephalometric Measurementsmentioning
confidence: 99%
“…There was no cleft defect. Imaging evaluation of the morphological airway changes has been performed in patients with OSA using techniques such as cephalometric radiography, CT, and magnetic resonance imaging [9][10][11]. CT scans though can create 3D images, exposes the child to ionizing radiation naturally experienced during approximately 8 months.…”
Section: Discussionmentioning
confidence: 99%
“…A região RL se estende da ponta da úvula à base da epiglote (11) . Muitos estudos têm sido realizados na tentativa de demonstrar que o tamanho e a morfologia das estruturas que compõem as vias aéreas superiores e as dimensões das estruturas a ela adjacentes influenciam o calibre da via aérea superior dos pacientes com SAOS (5,6,(11)(12)(13)18,29,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) .…”
Section: Anatomia Das Vias Aéreas Superioresunclassified
“…Nos últimos anos, com o advento da TC multislice e com a maior disponibilidade destes aparelhos, a TC tem sido utilizada como método auxiliar no diagnóstico da SAOS, e vários estudos têm sido realizados nestes pacientes, o que vem facilitando o entendimento da patogênese desta entidade (24,33,39,41,44) .…”
Section: Tomografia Computadorizadaunclassified